Kepastian Hukum Atas Pemeriksaan Setempat Terhadap Sengketa Tanah Dalam Perkara Perdata - Benu, Marthen; Ali, Moh.; Tektona, Rahmadi Indra (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
The mechanism for resolving land rights disputes in the District Court is always handled by a judge, and before reaching an examination with an evidentiary agenda, the parties to the case will carry out efforts at peace or mediation. The judge/judicial panel, clerk/substitute clerk, and bailiff/substitute bailiff together with the parties present go to the location of the object to be inspected and carry out the inspection. The first thing that is asked for information is from the plaintiff in accordance with the contents of the lawsuit. The local inspection carried out by the judge has the function of assisting the judge in making his decision. The problems that arise are related to the role and function of the local inspection of the disputed object in the form of land if it is related to the construction of evidence in civil cases The problem formulation in this research is (1) Has the local examination of the object of a land dispute in a civil case provided legal certainty? (2) What are the legal implications of a local examination of a civil case object? and (3) What is legal certainty in future arrangements for local inspections of land objects in civil cases. From the results of the research carried out, it was found that local inspections were based on Article 153 HIR, Article 180 RBg and Articles 211 – 214 Rv and SEMA No. 7 of 2001 does not yet reflect legal certainty because it does not regulate in detail the local inspection mechanisms in the field, giving rise to multiple interpretations. Apart from that, the local examination is still ambiguous as to whether it is evidence whose evidentiary value is left to the judge or whether the local examination is not included in the category of evidence, it is an examination tool or method to obtain evidence. The results obtained in the local inspection are valid evidence. The legal implications of a local examination of a civil case object are (1) on the costs of the case if the judge desires a local examination, (2) on the evidentiary strength of the local examination. These two things contain legal consequences that need to be clarified in future regulatory aspects. Legal certainty in the future regulation of local inspections of land objects in civil cases is that all cases involving immovable objects such as land must be carried out locally and preferably carried out after further examination of evidence to overcome differences in the practice of carrying out local inspections. Uniformity of these arrangements is very important to create legal certainty regarding local inspections. Regulations regarding local examinations must be established at the statutory level so that they have strong binding power on all parties involved in the case, including judges, clerks and all.